Reforming the Legislation on Administrative Offences - A. G. Avdeiko; D. A. Gazizov (Сибирское юридическое обозрение, 2019)
The article is devoted to the analysis of current trends in the development of material and procedural norms of the legislation on administrative responsibility in the context of attempts to develop a new model of the code governing administrative responsibility in the Russian Federation. The complex of important problems existing in this field is investigated. The necessity of reforming the legislation on administrative offenses is substantiated, ideas and prospects for the development of a new codified act in the relevant legal industry are presented. The Authors of the article come to the conclusion that it is necessary to create the concept of an appropriate draft federal law, which allows for a balance between the constitutional principles for protecting the rights and freedoms of citizens and the simplicity and speed of the procedure of bringing perpetrators to administrative responsibility.